Kombinirani transport - izazov i ponuda za budućnost - Mađarić, Juraj; Božićević, Damir (Promet - Traffic&Transportation, 2012)
Upon providing the information on the work of the I. European Forum on Combined Transport - EUROMODAL 90 - held in Brussels earlier this year, the authors deal with the achievements of the INTERCONTAINER Railway Society in the process of development of container transport in Europe as well as the achievements of the German Railways in the development of combined rail and road transport mode. Special reference is made to the issues of piggy-back and its development in Europe per individual techniques to provide a detailed presentation ·of characteristics and advantages of new technology (techniques) of piggy- back mode, the so called bi-modal system and reiterate its economic effects and recommend its application in Yugoslavia.